Endovascular Repair of Persistent Sciatic Artery With Limb Ischemia: A Wrong Choice? - Deng, Liming; Deng, Zhihe; Chen, Kaiyu; Chen, Ziyan; Chen, Gang; Xiong, Guozuo (Frontiers in Surgery, 2020)
Objectives: Persistent sciatic artery (PSA) is a rare congenital malformation that could lead to serious complications such as lower extremity ischemiais. We report the treatment of a PSA patient combined with limb ischemia. Methods: A 64-year-old man was admitted to the hospital for intermittent claudication of the right lower limb. The right ankle–brachial index (ABI) was 0.5. Computed tomography angiography (CTA) revealed the presence of an incomplete PSA with an absence superficial femoral artery. We performed catheter-directed thrombolysis (CDT) and stenting placement for the patient. Results: The vessels were successfully opened, and the claudication was resolved. However, half a year after the operation, the right PSA of the patient was occluded. Conclusion: The etiology, pathophysiology, and anatomic factors should be considered in the treatment of PSA. Endovascular treatment, bypass surgery, and drug therapy should be balanced. Improper choice of any treatment regimen may result in poor prognosis.